Effectiveness of Kersen Leaf Extract Cream (Muntingia calabura L.) on The 3rd Day of Incision Healing Process on The Skin of Streptozotocin Induced White Rats (Rattus norvegicus) - Salim, M. Nur; Azhar, Nurul Sakinah; Masyitha, Dian; Vanda, Henni; Rosmaidar, Rosmaidar; Zainuddin, Zainuddin (Universitas Syiah Kuala, 2024)
A wound is a break in the continuity of tissue, which physiologically undergoes several phases of healing: hemostasis, inflammation, proliferation, and maturation. The wound healing phase can be prolonged if one experiences metabolic disorders such as diabetes mellitus (DM). Treatment is necessary to prevent the prolongation of the wound healing phase in DM patients, one of which involves using traditional medicine, specifically cherry plants. This study aimed to determine the effectiveness of cherry leaf extract cream in the healing process of incision wounds on day 3 on the skin of white rats induced by streptozotocin. The samples used were 12 white rats, aged approximately 3 months, with a body weight of 179.25 12.64 g. The rats were injected intraperitoneally with streptozotocin at a dose of 45 mg/kg BW. After 72 hours, an incision was made in the paravertebral section with a length of 2 cm and a depth reaching the subcutaneous layer. Therapy was administered for 3 days in several groups. Group KI served as the negative control (cream base), KII as the positive control (metformin 4.5 mg/kg BW and silver sulfadiazine 0.1% cream), KIII (2 ml cherry leaf extract and topical therapy with 5% cherry leaf extract cream), and KIV (2 ml cherry leaf extract and 15% cherry leaf extract cream). The results of the average number of inflammatory cells in KI, KII, KIII, and KIV were 117.403.17; 87.878.97; 104.405.97; and 91.405.39, respectively, with P0.05. The average number of new blood vessels in KI, KII, KIII, and KIV were 1.070.64; 4.870.64; 5.800.80; and 6.001.31, respectively, with P0.05. The conclusion of this study is that the administration of cherry leaf extract and 15% cherry leaf extract cream can reduce inflammatory cell infiltration and accelerate the growth of new blood vessels